Mortality and detailed characteristics of pre-ICU qSOFA-negative patients with suspected sepsis: an observational study - Izumi Nakayama (Annals of Intensive Care, 2018)
Abstract Background Recent studies have suggested that quick Sequential Organ Failure Assessment (qSOFA) scores have limited utility in early prognostication in high-mortality populations. The purpose of this study was to investigate the association between pre-ICU qSOFA scores and in-hospital mortality among patients admitted to the ICU with suspected sepsis. This study also aimed to describe detailed clinical characteristics of qSOFA-negative (< 2) patients. Methods This single center, observational study, conducted in a Japanese tertiary care teaching hospital between May 2012 and June 2016, enrolled all consecutive adult patients admitted to the ICU with suspected sepsis. We assessed pre-ICU qSOFA scores with the most abnormal vital signs during the 24-h period before ICU admission. The primary outcome was in-hospital mortality censored at 90 days. We analyzed the association between pre-ICU qSOFA scores and in-hospital mortality. Results Among 185 ICU patients with suspected sepsis, 14.1% (26/185) of patients remained qSOFA-negative at the time of ICU admission and 29.2% (54/185) of patients died while in hospital. In-hospital mortality was similar between the groups (qSOFA-positive [≥ 2]: 30.2% [48/159] vs qSOFA-negative: 23.1% [6/26], p = 0.642). The Cox proportional hazard regression model revealed that being qSOFA-positive was not significantly associated with in-hospital mortality (adjusted hazard ratio 1.35, 95% confidence interval 0.56–3.22, p = 0.506). Bloodstream infection, immunosuppression, and hematologic malignancy were observed more frequently in qSOFA-negative patients. Conclusions Among ICU patients with suspected sepsis, we could not find a strong association between pre-ICU qSOFA scores and in-hospital mortality. Our study suggested high mortality and bacterial diversity in pre-ICU qSOFA-negative patients.